Salvage STA-MCA bypass surgery in an adult moyamoya patient after failed indirect revascularization surgery. (2nd November 2015) - Yoo, Minwook; Jin, Sung-Chul; Jin, Seong-Jin; Choi, Byeong-Sam
Abstract : A 39-year-old female moyamoya disease patient underwent a salvage direct bypass surgery involving anastomosis of the superficial temporal artery or STA and middle cerebral artery or MCA. This report describes a rare case of moyamoya disease that was revascularized after the previous indirect bypass surgery failed to restore collateral blood flow.